ANALISIS PENERIMAAN PAJAK BAHAN BAKAR KENDARAAN BERMOTOR DAN KONTRIBUSINYA TERHADAP BADAN PENDAPATAN DAERAH PROVINSI KALIMANTAN TENGAH - Nada Okta Anugrah; Enny Hardi; Sustinah Limarjani (Universitas Lambung Mangkurat, 2021)
To find out and analyze PBBKB receipts in Central Kalimantan Province for the 2018 to 2020 fiscal year and the development of contributions by 2018 to 2020 regional budget revenues are the objectives of this study. The results of this study indicate that the percentage in 2018 shows the highest percentage compared to 2018 to 2020 and the smallest contribution percentage is in 2020. The percentage of contributions given is not the same as the nominal PBBKB revenue and regional income in budget recording and final realization. year.